Amor Fati and Memento Mori in Marcus Aurelius’ Meditations: The Synthesis of Stoicism - Bhandari, Sabindra Raj (Journal of NELTA Gandaki, 2022)
This article examines the philosophy of Stoicism in Marcus Aurelius’ philosophical work Meditations. Stoicism empowers us to embrace the pleasures and pains that come in our life without any reaction. It creates a mental disposition that leads to the stage of equanimity. Meditations exposes the power of stoic virtues like Amor fati (love of fate) and the Memento Mori (remember that you will die). These virtues pave the path for the cardinal virtues like wisdom, moderation, courage, and justice. The stoic virtues make us realize that we are in the abyss of infinity, and we do not exist only for ourselves. Aurelius’ Meditations muses on these great mysteries of life, echoing the vibrations of eastern and western lyre of Stoic philosophy. This article implements a qualitative approach to research, and interpretive paradigm to crystallize the radiance of stoic wisdom in Meditations. It is equally significant to discuss the applications of Stoic norms in the pedagogy that transform the junior citizens into the new humans to face the challenges of the modern age.